Global impact of KRAS mutation patterns in FOLFOX treated metastatic colorectal cancer - Zocche, David M. (Front Genet, 2015)
Background: Colorectal cancer (CRC) is one of the most frequent events in oncology. Advances in molecular understanding of the processes of carcinogenesis have shed light on the fundamental mechanisms of tumorigenesis. Currently, knowledge of the molecular basis of its pathogenesis is being used to improve patient care and devise more rational therapeutics. Still, the role played by the mutation patterns of mutated genes in the clinical outcomes that patients on pharmacological treatment receive remains unclear. In this study, we propose to analyze the different clinical outcomes and disease prognosis of patients with stage IV CRC treated with FOLFOX chemotherapy (fluorouracil, leucovorin, oxaliplatin) based on different Kirsten ras (KRAS) mutation patterns. Methods: In this cohort study, 148 patients diagnosed with stage IV CRC and treated with FOLFOX were studied between 2008 and 2013. Mutational status of KRAS was determined. Progression-free survival (PFS) and overall survival (OS) were measured, and all deaths were verified. Survival analysis was performed using Kaplan–Meier analysis, comparison among groups was analyzed using the log-rank test, and multivariate analysis was conducted using Cox proportional-hazards regression. Results: Among a total of 148 patients, 48 (32%) had mutated KRAS, 77% at codon 12 and 23% at codon 13. The PFS was significantly worse in the mutant KRAS patients in comparison to wild type KRAS patients (p < 0.05). The OS did not show significant differences between the two groups. Multivariate analysis showed KRAS mutation as an independent negative prognostic factor for PFS. Among the various subtypes of KRAS mutation, G12D was significantly associated with a poor prognosis in PFS (p = 0.02). Conclusion: In our population, the KRAS mutation had an adverse impact on the prognosis for stage IV CRC patients treated with the FOLFOX regimen.